2018
DOI: 10.1111/petr.13238
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for persistent hyperparathyroidism in children with stable renal function after kidney transplantation

Abstract: This study aimed to investigate the risk factors for PHPT in children with stable renal function who received KT. We retrospectively analyzed the clinical findings and laboratory results of patients who underwent KT below 19 years of age, between 1996 and 2016 at our hospital. Patients were followed up for more than 1 year after KT. We calculated the mean ± standard deviation or median [minimum - maximum] for each parameter. We included a total of 46 patients (male:female = 26:20). Twelve patients (26.1%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…2 Multiple studies have indicated a strong correlation between dialysis vintage and HPT. 3,4,6,7,21 Both prolonged dialysis vintage and severe HPT are detrimental to growth, long-term cardiovascular and bone health in children, thus underscoring the need to encourage preemptive transplantation in children. Secondary HPT is an important contributor to MBD, commencing as early as CKD stage 2 in some children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Multiple studies have indicated a strong correlation between dialysis vintage and HPT. 3,4,6,7,21 Both prolonged dialysis vintage and severe HPT are detrimental to growth, long-term cardiovascular and bone health in children, thus underscoring the need to encourage preemptive transplantation in children. Secondary HPT is an important contributor to MBD, commencing as early as CKD stage 2 in some children.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been associated with HPT including longer dialysis vintage and greater severity of pre-transplant HPT. 3,4,6,7 Long-standing secondary HPT before transplantation can lead to autonomous functioning of the parathyroid glands resulting in tertiary HPT, which is clinically manifested by hypercalcemia. Parathyroid hyperplasia develops when secondary HPT is prolonged and may lead to nodular hyperplasia and adenoma formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with pre-KT PTH levels of 300-599 pg/mL are likely to develop PHPT, and the higher the preoperative level, the more possibility PHPT developing (22). In addition, a dialysis vintage > 6 years is a strong predictor of PHPT (21,42). The parathyroid mass grows gradually and progresses over time in patients undergoing long term dialysis, indicating a high possibility of parathyroid gland autonomy (42).…”
Section: 2mentioning
confidence: 99%
“…Nevertheless, comprehensive data on persistent hyperparathyroidism among children undergoing KT are limited [17,18]. Only a few studies in Asia have examined the epidemiology of persistent hyperparathyroidism and its risk factors among children [19].…”
Section: Introductionmentioning
confidence: 99%